A CONTRASTIVE STUDY OF THE METAPHOR USED IN ENGLISH AND VIETNAMESE FOLK SONGS - NGUYỄN NGỌC ÁI QUỲNH (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigated into the semantic features of metaphors in English and Vietnamese folk songs. Under the framework of cognitive linguistics, we looked into how English and Vietnamese made use of metaphors in reference to conceptual metaphor in the idealized conceptual models. We found that English and Vietnamese share a lot of entities in the mappings concerning the use of metaphors by poets and composers. Basing on the findings and results of this study, some implications for the teaching and learning of English will also be suggested.